Helium-deficient ER UMa-type Dwarf Nova below the Period Minimum with a Hot Secondary - Youngdae Lee; Dae-Sik Moon; Sang Chul Kim; Hong Soo Park; Yuan Qi Ni (The Astrophysical Journal, 2024)
We present the discovery of a peculiar dwarf nova KSP-OT-201712a using high-cadence, multicolor observations made with the Korea Microlensing Telescope Network. KSP-OT-201712a exhibits a rare presence of outbursts during standstills, as well as strong H α emission for a dwarf nova below the period minimum with an orbital period of 58.75 ± 0.02 minutes. The outburst cycles are ∼6.6 days within standstills but increase to ∼15 days outside of them. Both B − V and V − I colors become bluer and redder as the outburst luminosities increase and decrease, respectively, for the outburst within standstill, while they evolve in the opposite directions outside of the standstills. The presence of strong double-peaked H α and weak He i emission lines with He/H flux ratio of 0.27, together with absorption lines of Mg b and Na D in the source, leads to the estimation T _eff ≃ 4570 ± 40 K, [Fe/H] ≃ 0.06 ± 0.15 dex, and log g ≃ 4.5 ± 0.1 for its secondary. KSP-OT-201712a is the second He-deficient dwarf nova below the period minimum, while the temperature of the secondary is measured for the first time in such objects. We identify it to be an ER UMa-type dwarf nova, suggesting that the evolution of dwarf novae across the period minimum is accompanied by large mass transfers. The high temperature of the secondary indicates that the system started its mass transfer when the secondary was about 93% of its main-sequence age. The system will evolve to a helium cataclysmic variable or to AM CVn once its hydrogen envelope is exhausted before it explodes as a Type Ia supernova.